ENTRE ESCRITAS E CAMINHOS FORMATIVOS: A DOCÊNCIA COMO POSSIBILIDADE DE PARTILHA - Afonso, Mariângela da Rosa; Dutra, Eduarda Vesfal; Ribeiro, José Antonio Bicca (Revista Didática Sistêmica, 2026)
The manuscript presents a reflection on teacher education in Physical Education, developed through three acts written as letters by a university Professor, a postdoctoral Professor, and a doctoral student. Drawing on Freirean pedagogy, the phenomenology of the body, and autobiographical narratives, the text highlights teaching as a dialogical, sensitive, and collective process. The writings intertwine personal and professional experiences, portraying teacher education as a journey marked by memories, affections, and shared experiences that generate experiential knowledge. The authors discuss the formative role of writing, the body, and encounters, emphasizing the importance of listening, care, and criticality in higher education. By valuing life histories and intergenerational bonds, the manuscript reaffirms teaching as an ethical, political, and human act, guided by meaning-making and the continuous reinvention of the teaching self.